2010
DOI: 10.4274/tjo.40.31
|View full text |Cite
|
Sign up to set email alerts
|

Application of Topical/Subconjunctival Bevacizumab and Topical Fluorometholone Acetate in Alkali Burn-induced Model of Corneal Angiogenesis

Abstract: Alkali yan›¤a ba¤l› geliflen korneal anjiogenez modelinde kornea neovaskülarizasyonu üzerine bevacizumab›n etkisini araflt›rmak. Gereç ve Yöntem: Çal›flmada 24 adet Wistar-Albino cinsi rat kullan›ld›. Kornealarda kimyasal koterizasyonu takiben ratlar tesadüfi olarak 4 gruba ayr›ld›. Grup 1'e (kontrol grubu) suni gözyafl› günde iki kez, grup 2'ye topikal florometolon asetat günde iki kez, Grup 3'e subkonjonktival bevacizumab 2,5 mg olarak tek doz, grup 4'e ise topikal bevacizumab günde iki kez 5 mg/ml konsantra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Dursun et al have shown that subconjunctival bevacizumab and ranibizumab treatments may be beneficial in reducing corneal NV. 33 Additionally, they claimed that bevacizumab had a greater inhibitory impact on corneal NV than ranibizumab. They demonstrated that the longest neovascular sprout length was substantially shorter in the bevacizumab and ranibizumab groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Dursun et al have shown that subconjunctival bevacizumab and ranibizumab treatments may be beneficial in reducing corneal NV. 33 Additionally, they claimed that bevacizumab had a greater inhibitory impact on corneal NV than ranibizumab. They demonstrated that the longest neovascular sprout length was substantially shorter in the bevacizumab and ranibizumab groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…В недавнем исследовании, проведенным A. Dursun и соавт. [46], площадь неоваскуляризации роговицы, вызванной щелочным ожогом, снижалась по сравнению с контрольной группой на 28% у пациентов, получавших субконъюнктивально бевацизумаб (2,5 мг), и на 21% у пациентов, получавших субконъюнктивально ранибизумаб (1 мг).…”
unclassified